Becoming DACAmented: Assessing the Short-Term Benefits of Deferred Action for Childhood Arrivals (DACA). (December 2014) - Gonzales, Roberto G.; Terriquez, Veronica; Ruszczyk, Stephen P.
In response to political pressure, President Obama authorized the Deferred Action for Childhood Arrivals (DACA) program in 2012, giving qualified undocumented young people access to relief from deportation, renewable work permits, and temporary Social Security numbers. This policy opened up access to new jobs, higher earnings, driver's licenses, health care, and banking. Using data from a national sample of DACA beneficiaries ( N = 2, 381), this article investigates variations in how undocumented young adults benefit from DACA. Our findings suggest that, at least in the short term, DACA has reduced some of the challenges that undocumented young adults must overcome to achieve economic and social incorporation. However, those with higher levels of education and access to greater family and community resources appear to have benefited the most. As such, our study provides new insights into how social policy interacts with other stratification processes to shape diverging pathways of incorporation among the general pool of undocumented immigrants.